2004
DOI: 10.1523/jneurosci.4530-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Climbing Fibers Control an Intrinsic Spike Generator in Cerebellar Purkinje Cells

Abstract: It is well established that the climbing fiber (CF) input to a cerebellar Purkinje cell (PC) can exert a controlling influence on the background simple spike (SS) activity of the cell, in that repetitive stimulation of CFs causes a decrease in SS activity, and removal or inactivation of CFs is followed by a rise in activity. In the present study, the effects of inactivation of CFs in the short term and longer term (hours) were investigated in anesthetized rats to determine how the CFs control the PC SS activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
124
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 41 publications
15
124
1
Order By: Relevance
“…Previous electrophysiological recording in isolated/slice preparations or in anesthetized animals indicated that Purkinje cells fire spontaneously in the absence of synaptic input (32)(33)(34). In contrast to these findings, blockade of granule cell transmission abolished firing of simple spikes in the DOX-treated awake animals.…”
Section: Discussionmentioning
confidence: 90%
“…Previous electrophysiological recording in isolated/slice preparations or in anesthetized animals indicated that Purkinje cells fire spontaneously in the absence of synaptic input (32)(33)(34). In contrast to these findings, blockade of granule cell transmission abolished firing of simple spikes in the DOX-treated awake animals.…”
Section: Discussionmentioning
confidence: 90%
“…Individual simple spikes are relatively ineffective at shunting ongoing synaptic potentials in Purkinje cells (Häusser et al, 2001), and thus the large synaptic and intrinsic conductances underlying the complex spike can provide a much more effective reset of synaptic integration. The wide range of spikelet numbers and frequencies possible at the soma, and their sensitivity to background excitation, may provide a more graded signal to fine-tune homeostatic mechanisms in the dendrites and proximal region of the axon (Cerminara and Rawson, 2004). Furthermore, because spikes are energetically expensive (Attwell and Laughlin, 2001), particularly when propagating over long distances, the limit on axonal firing may represent a protective mechanism to reduce the overall energetic costs of complex spike firing.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…We found a correlation between the average rate of the CFR and the number of EPSP components in a CFR, but whether the number of climbing fiber intraburst spikes plays a role in short-term changes in simple spike activity is not known. Such a function, if it exists, may also complement the role of climbing fibers in regulating the level of Purkinje cell simple spike firing (Colin et al, 1980;Cerminara and Rawson, 2004).…”
Section: Functions Of Climbing Fiber Burstsmentioning
confidence: 99%